Phthalocyanine-based coordination polymer nanoparticles for enhanced photodynamic therapy. Issue 41 (10th October 2017) - Huang, Ziyuan; Huang, Liangfeng; Huang, Yanjuan; He, Yuanfeng; Sun, Xiaoqi; Fu, Xiang; Xu, Xiaoyu; Wei, Gaofei; Chen, Dawei; Zhao, Chunshun
Abstract : The constructed nanoparticles solved the aggregation, low solubility and poor selectivity of zinc phthalocyanine along with high singlet oxygen yield. Abstract : In the photodynamic therapy (PDT) of cancer, zinc phthalocyanine (ZnPc) as a photosensitizer possesses superior photosensitive properties. However, the therapeutic effect of ZnPc in PDT is limited due to its aggregation, low solubility and poor selectivity. In this study, charge-reversal phthalocyanine-based coordination polymer nanoparticles (PCPN) are developed for improving the curative effect of ZnPc. Tetra(4-carboxyphenoxy)-phthalocyaninatozinc(ii ) (TPZnPc) is coordinated with the zinc ion to form the core of PCPN, which is coated with a lipid bilayer by self-assembly (PCPNs@Lip). TPZnPc molecules in the core of PCPN are in the monomeric state and can generate cytotoxic singlet oxygen ( 1 O2 ) efficiently, which solves the solubility and aggregation problems of ZnPc. Meanwhile, 1, 2-dicarboxylic-cyclohexane anhydride modified lysyl-cholesterol (DLC) is functionalized on the surface of PCPN (PCPNs@Lip/DLC), endowing PCPN with a charge-reversal ability which could be triggered by a mildly acidic tumor microenvironment. PCPNs@Lip/DLC is proved to enhance tumor cellular uptake and generate more intracellular 1 O2 after irradiation. As confirmed by in vitro and in vivo studies, PCPNs@Lip/DLC remarkably increases the PDT effect. All these results demonstrate that PCPNs@Lip/DLC is a promising nanoplatform for the application of ZnPc in effective PDT.